2017
DOI: 10.1108/yc-05-2017-00697
|View full text |Cite
|
Sign up to set email alerts
|

Do consumer ethics and consumer religiousness evolve across time? Insights from Millennials in Indonesia

Abstract: Purpose The Millennial generation accounts for 27 per cent of the world’s population. These numbers highlight the current and future impact of Millennials on world economies, and they are arguably the most powerful consumer group. Interestingly, Millennials are also the least religious generation. Hence, there is a need to investigate further how they view the world from an ethical and religious perspective and whether their beliefs evolve over time. Therefore, the purpose of this study is, first, to compare a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
1
9
0
1
Order By: Relevance
“…Studies have investigated the contributing factors of consumers’ ethical beliefs such as religion (Arli & Tjiptono, ; Arli, Tjiptono, Lasmono, & Anandya, ; Vitell, ; Vitell et al, ); moral philosophy (Lu & Lu, ); materialism (Muncy & Eastman, ; Tang & Chen, ; Vitell et al, ); gender (Bateman & Valentine, ); acculturation (Pekerti & Arli, ; Swaidan, Vitell, Rose, & Gilbert, ; Swaidan, ); and personality trait (Rallapalli, Vitell, Wiebe, & Barnes, ). Nonetheless, there are still limited studies investigating the role of Machiavellianism on ethical beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have investigated the contributing factors of consumers’ ethical beliefs such as religion (Arli & Tjiptono, ; Arli, Tjiptono, Lasmono, & Anandya, ; Vitell, ; Vitell et al, ); moral philosophy (Lu & Lu, ); materialism (Muncy & Eastman, ; Tang & Chen, ; Vitell et al, ); gender (Bateman & Valentine, ); acculturation (Pekerti & Arli, ; Swaidan, Vitell, Rose, & Gilbert, ; Swaidan, ); and personality trait (Rallapalli, Vitell, Wiebe, & Barnes, ). Nonetheless, there are still limited studies investigating the role of Machiavellianism on ethical beliefs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of the holy verse as a behavioral reference is still well preserved at all ages, including young people. Arli et al, (2017) observed the impact of religiosity on consumer ethics among young people [22]. The results of his research mention that young people understand the boundary between legal and illegal behavior.…”
Section: Resultsmentioning
confidence: 97%
“…By using academic language, the scriptures can be positioned as scientific law. Davis and Carter (2009) concluded that overeating has similarities with drug addiction [22]. This conclusion is based on comparable clinical trials, the biological mechanisms they have and the evidence that the two disorders share the same characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the holy verse as a behavioral reference is still well preserved at all ages, including young people. Arli [10] observed the impact of religiosity on consumer ethics among young people. The results of his research mention that young people understand the boundary between legal and illegal behavior.…”
Section: Resultsmentioning
confidence: 99%